1988
DOI: 10.1177/152808378801700303
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethanes for Flexible Surface Coatings and Adhesives

Abstract: Polyurethanes can be tailor-made for a wide range of flexible surface coatings, e.g., for textile substrates and leather; and for a wide variety of adhesives. Polyurethanes give unexcelled performance in almost all of these applications. A prime target of coating textiles with polyurethanes is the achievement of the quality of natural leather. A highly water vapor permeable, but water repellent textile coating has recently become possible using a direct coating process. The application of a micro porous polyur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…It is observed that the percentage elongation increases with increase in the molecular weight of polyurethanes [3,4].…”
Section: Percentage Of Elongationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed that the percentage elongation increases with increase in the molecular weight of polyurethanes [3,4].…”
Section: Percentage Of Elongationmentioning
confidence: 99%
“…Each of these three has a direct bearing on the properties of the polyurethanes synthesized. The polyols and diisocyanates form the backbone of the molecular chain of the polymer, which is responsible for its ultimate performance properties such as mechanical properties, abrasion resistance,¯exural endurance and resistance to chemicals and hostile environments [3,4]. The end use requirement is met by varying these three types of material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties make TPU an attractive material for coated textiles (9) or for leather like products (10). These TPU coated textiles are used for inflatable boats, flexible tanks or more technical applications like Lighter-Than-Air systems for high altitude applications (11).…”
Section: Introductionmentioning
confidence: 99%
“…In the application of breathable-coated fabrics, the polyurethane film has become an important element [11][12][13][14][15] . However, these materials are generally not thermally very stable, especially above their softening temperature [16,17] .…”
Section: Introductionmentioning
confidence: 99%